2004
DOI: 10.24310/abm.v29i0.7229
|View full text |Cite
|
Sign up to set email alerts
|

Endodermis foliares en el género Isoetes L. (Isoetaceae).

Abstract: RESUMEN. Endodermis foliares en el género Isoetes L. (Isoetaceae). La presencia y naturaleza de la endodermis en microfilos de 18 taxones de Isoetes se puso de manifiesto con técnicas microquímicas de coloración con TBO y mediante fluorescencia intrínseca (autofluorescencia). Las especies estudiadas son: I. adspersa, I. andina, I. boliviensis, I. boryana, I.brochonii, I. durieui, I. echinospora, I.engelmanii, I. histrix, I. lacustris, I. lechleri, I. longissima, I. malinverniana, I. melanopoda, I. setacea, I. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…Hall (1971) sugirió que los canales llevan agua y no aire. Esta es una interesante afirmación en relación con lo anterior, ya que el mayor número de canales intrastelares en plantas anfibias o terrestres podría relacionarse con la necesidad obvia en éstas de evitar que los tejidos vasculares se inunden periód-icamente, una función a la que contribuye la presencia de endodermis en los canales (Rolleri & Prada, 2004).…”
Section: Discusió Nunclassified
“…Hall (1971) sugirió que los canales llevan agua y no aire. Esta es una interesante afirmación en relación con lo anterior, ya que el mayor número de canales intrastelares en plantas anfibias o terrestres podría relacionarse con la necesidad obvia en éstas de evitar que los tejidos vasculares se inunden periód-icamente, una función a la que contribuye la presencia de endodermis en los canales (Rolleri & Prada, 2004).…”
Section: Discusió Nunclassified
“…Previous studies showed that several anatomical traits of Isoëtes leaves, such as the number of interstellar canals, the shape of the translacunar diaphragm cells, the presence of intercellular pectic protuberances, peripheral fibrous strands, stomata, cuticular ornamentations, and the sporangium epidermis coloration, have diagnostic value (Pfeiffer 1922;Hall 1971;Prada 1979Prada , 1983Takamiya et al 1997;Kott & Britton 1985;Hickey 1986;Taylor & Hickey 1992). Fluorescence and scanning microscopy techniques were used to document and categorize the endoderm of the interstellar canals and the aerenchyma lacunae (Romeo et al 2000;Rolleri & Prada 2004) and the intercellular pectic protuberances (Prada & Rolleri 2003;Rolleri & Prada 2005). In addition to qualitative traits, micro-morphometric leaf parameters have also been identified as taxonomically important (Budke et al 2005;Rolleri & Prada 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Literature on Isoetes and keys to the species of the genus normally rely on a few characters, mostly related to habit, plant size, corm lobing, velum cover, spore size and ornamentation, and more recently, chromosome number. Based on previous studies made on Isoetes (Hall, 1971;Marsden, 1976;Prada, 1979;Prada & Rolleri, 2003;Rolleri & Prada, 2004; C. H. Rolleri & C. Prada, unpubl. data) several additional foliar characters are used here to identify taxa in the genus. These characters are: cuticular ornamentation, presence or absence of cuticular pegs, types of margin, epidermal patterns of microphylls, stomata, transverse sections of microphylls, number and distribution of collenchymatous strands in the mesophyll, presence and types of intercellular pectic protuberances (IPP) of the cells of the translacunar diaphragms, presence of a partial or complete foliar endodermis at the air chambers and intrastellar canals of the leaves (Rolleri & Prada, 2004), and epidermal patterns of sporangium adaxial wall.…”
Section: Introductionmentioning
confidence: 99%
“…Literature on Isoetes and keys to the species of the genus normally rely on a few characters, mostly related to habit, plant size, corm lobing, velum cover, spore size and ornamentation, and more recently, chromosome number. Based on previous studies made on Isoetes (Hall, 1971; Marsden, 1976; Prada, 1979; Prada & Rolleri, 2003; Rolleri & Prada, 2004; C. H. Rolleri & C. Prada, unpubl. data) several additional foliar characters are used here to identify taxa in the genus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation